Fragmentation of 1.2A GeV/c 10C in nuclear emulsion - Bekmirzaev, Rahmatulla; Ulasheva, Mashxura; Abduvaxobov, Xondamir; Nabiev, Bahodir (Физико-технологического образование, 2021)
It is discussed the experimental results and their comparison with multi-source thermal model calculations by fragmentation of isotope 10C to much lighter nuclear such as 8Be, 4 He and etc. Conclusions obtained basing on investigation and angle distribution analysis fragments relative direction projectile particles and also spectrum of distribution on transverse momentum of fragments from 10C allows possibility of using multi-source thermal model at energy of interactions 1.2 A GeV.